Identification of thermal process of electric double layer capacitor systems by distribution of relaxation times analysis for thermal impedance spectroscopy. (1st August 2023) - Li, Zetao; Feng, Huihua; Jia, Boru; Zuo, Zhengxing; Mei, Bing-Ang
Abstract: Identification of thermal process is important for obtaining the thermal parameters of electric double layer capacitors. This study applies distribution of relaxation times (DRT) analysis for physical interpretation of the thermal impedance spectroscopy measurement of EDLC systems. Three distinct peaks are observed in the DRT plots of the electrode systems. The peak area represents the thermal resistance contribution of different thermal processes, while the time constant of peak center represents the speed of each process. The results indicate that the peaks from short to long time constant can be attributed to heat conductions in solid, interfacial, and fluid-involved paths, respectively. In addition, the area of peaks are strongly affected by the compression of electrode. This is attributed to the variations in total thickness and cross-sectional area of the system. Finally, replacing the fluid from air to electrolyte or changing solid–fluid ratio in two-phase region can lead to a remarkable shift in time constant of fluid-involved heat transfer peak. Graphical abstract: Highlights: DRT analysis was applied for thermal process identification of electric double layer capacitors. Three distinct peaks were observed in the thermal DRT plots of porous electrode systems. Solid, interfacial, and fluid-involved heat flow paths were assigned to three peaks. Compression of electrodes strongly affected the peak area in thermal DRT plots. Variety and ratio changes of fluid led to a time-constant shift in thermal DRT plots.